Nivel de aptitud funcional en mujeres no institucionalizadas mayores de 60 años de una ciudad de España (2015)
ABSTRACT: Decrease in functional fitness (FF) in older persons is associated with a greater dependence and disability. This is an area of interest in the current context of global aging and Spain. Objective: determine the level of FF in a group of non-institutionalized women over 60 years old from a city of Spain. Materials and methods: a cross-sectional study was carried out in 176 women. The FF was determined by four of the senior fitness test (SFT): arm curl test, chair stand, 2-min step test and ‘8 foot upand-go test’. The low FF was defined from standardized cut points by Rikli & Jones (2013). Grip strength was included as another FF test. Results: the low AF was more frequent in ‘arm curl test’ and the grip strength (21.0% and 15.9% respectively) and the lowest decrease was “chair stand” with 7.4%. The FF decreased with increasing age, showing a significant difference from 75 years (p <0,05). Obese persons had lower FF in ‘2-min step test’ and ‘8 foot up-and-go test’ (p <0.05). Conclusion: upper limb strength was the lowest performing parameter while increasing in age and condition of obesity are associated a decrease in the FF. The evaluation of the FF is a useful tool in the diagnosis of health status in the elderly. More research is needed by aiming at the standardization of cut points associated with low FF in Spanish population.